IMPLEMENTATION OF THE SIMPLE ADDITIVE WEIGHTING (SAW) METHOD FOR SELECTION OF SALESPERSON - Jefri Rahmadian; Julia Fajaryanti; Rogayah Rogayah (Universitas Teknokrat Indonesia, 2023)
The purpose of this study is to apply the Simple Additive Weighting (SAW) method in determining the best salesperson at XYZ company in terms of sales performance. This SAW method is considered very suitable in determining the best salesperson because the SAW method carries out a weighted summation process based on the performance rating of each alternative on all existing attributes. The calculation process for selecting the best salesperson is carried out based on criteria that have been determined by the company based on the results of discussions and each criterion has weight. In the best salesperson assessment, the Company determines the criteria that become a reference in decision making. The criteria used are total sales, attendance, product knowledge, communication, and creativity. The results of the calculation of the final score obtained by the best salesperson ranked 1st were Rangga Dwi Nugroho getting a final score of 0.9. Rank 2 Nurlia Arbaini got a final score of 0.8436. And in 3rd place, Defri Akbarias got a final score of 0.8364. From the results of these calculations, it shows that the SAW method has provided more effective results in terms of providing the best salesperson assessment results, so this is a very important information for company leaders in determining outstanding salesperson based on existing criteria using the SAW method.